The ITU and Managing Satellite Orbital and Spectrum Resources in the 21st Century - Allison, Audrey L. (SpringerBriefs in Space Development,, 2014)
Access to satellite orbits and spectrum is managed by the ITU, a United Nations body that strives to extend the benefits of new technologies to the world, while ensuring equitable access to these resources. This book explores how the ITU approaches these dual missions in light of the increasing saturation of the geostationary orbit by a vibrant global satellite industry and the rising interests of developing countries in accessing these limited resources. These issues were the subject of debate at the 2012 World Radiocommunication Conference. This book describes and assesses various regulatory approaches undertaken to manage the increasing requests for access to space and especially access to spectrum and orbital locations in the geosynchronous or "The Clarke" orbit.